Proces motywowania i warunki jego skuteczności w przedsiębiorstwie - Penc, Józef (Wydział Prawa i Administracji UAM, 1988)
Human conduct is in particular circumestances determined by a set of interconnected motives constituting motivation. Motivation needs to be purposefully shaped through creating for employees means and motivating situations which enable them to attain preferred values. Among such values a special role is played by remuneration which is necessary to fulfill various needs of an employee and his/her family. Remuneration may and should be an important factor of stimulating motivation and directing productive behaviour of people. However, if it is to perform such a role, specific rules concerning the composition and forms of application of pay must be observed, and various reinforcing activities indirectly influencing its motivating function must be undertaken. Its efficient fulfillment of such a function, i.e. the function of stimulating productivity and quality of work, depends on the following factors: buying power of money, actractiveness of the market, ways of obtaining raises in pay, a system of pay promotion in force, a structure of needs satisfied by means of pay, spread of income differentiation and ways of its reduction, connection between pay and effectiveness of work, forms of remuneration, internal structure of pay and psychophysical characteristics of employees, defining the level of their readiness to work depending on their living and working conditions. All those factors exert an influence in many ways and to a different degree on the employees' motivation, on its direction and intensity. It is indispensable to know and employ those factors in the process of motivating, for only an integral, systematic approach to motivation may guarantee its correct understanding and application in managing the work process and in increasing the employees' committment in their work and duties.
The process of motivating and conditions of its efficiency in an enterprise